Pengaruh Diferensiasi Produk dan Brand Equity Terhadap Keputusan Pembelian (Survei pada pengguna samsung galaxy A01 Core) - Siska Widia Obaita; Michelle Bulan Paramitta; Reminta Lumban Batu (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to analyze the effect of product differentiation and brand equity on purchasing decisions. This analysis uses independent variables, namely product differentiation and brand equity. The dependent variable is the purchase decision. The research method used in this research is descriptive analysis method and verification. The population in this study were users of the Samsung Galaxy A01 Core, with a total sample of 100 respondents. The sampling technique used is simple random sampling. Data collection techniques used in this study are primary data and secondary data. This research was conducted with the help of the SPSS 22 For Windows application. The data analysis technique used is multiple linear regression analysis. The results of the study state that there is a simultaneous effect of product differentiation and brand equity on purchasing decisions.